Vitamin D and Phagocytic Function in Patients with Sepsis: A Cross-Sectional Study - Lihartanadi, Jimmi; Mulya, Deshinta Putri; Humardewayanti, Rizka (Gaceta Médica de Caracas, 2023)
Background: Sepsis is a leading cause of mortality in intensive care units. Several recent studies have shown that Vitamin-D deficiency is associated with the malfunctioning of macrophages and neutrophils. We determined whether Vitamin D levels affect phagocyte function in patients with sepsis. We evaluated serum vitamin-D levels and phagocyte function in patients with sepsis in Dr. Sardjito Hospital. Method: The sample was 38 adult patients treated with sepsis from June to November 2018.